Some clinical lessons from one Blood and Marrow Transplantation Unit in Medellin, Colombia - CUELLAR-AMBROSI, Francisco; Monsalve Moreno MD, Mónica; Urrego Grisales, Beatriz; Cuervo Sierra, Jorge; Gaviria Cardona, Guillermo; Naranjo Serrano, Vanessa; Cuéllar-Garcia, Carolina (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2021)
After more than 60 years of the first successful bone marrow transplant (BMT) by D.E. Thomas for the treatment of hematological malignant diseases and more than 46 years since the first bone marrow transplant by Alberto Restrepo-Mesa in Medellin-Colombia for the treatment of a female triplet patient with paroxysmal nocturnal hemoglobinuria and aplastic anemia, in Colombia only around 750 bone marrow transplants are performed annually. With the experience accumulated during these years by each one of us, the León XIII Clinic of the Universidad de Antioquia began the hematopoietic stem cell transplantation (HSCT) program for adults in 2014. In this review, we report some clinical lessons drawn from the different phases of the HSCT in 109 adult patients with hematological malignancies. The progression-free survival (PFS) and the five-year overall survival (OS) were for autologous stem cell transplantation (ASCT) (87% and 70%), allogeneic stem cell transplantation (Allo SCT) (50% and 40%) and haploidentical stem cell transplantation (Haplo SCT) (25% and 18%) respectively.